Educational Leadership in Madrasah Aliyah (MA) Al-Huda in the Perspective of the Qur'an Surah An-Nisa Ayat 58 and Ali ‘Imron Ayat 159 - Yusli (Indonesian Journal of Islamic Education Studies (INJURIES), 2025)
This study aims to explore the understanding of the concept of educational leadership applied in Madrasah Aliyah Al-Huda, using the perspective of the Qur'an, especially Surah An-Nisa verse 58 and Surah Ali 'Imran verse 159. In Surah An-Nisa verse 58, Allah SWT emphasizes the importance of trust and justice in carrying out duties as a leader, which is the main foundation in educational leadership. Meanwhile, in Surah Ali 'Imran verse 159, the Qur'an teaches the importance of the nature of forgiveness, humility, and deliberation in carrying out leadership, which are the basic principles in the relationship between the leader and the led. This research uses a qualitative approach with a case study method at MA Al-Huda. Data was collected through interviews with 8 informants consisting of 1 madrasah head, 3 teachers, 2 administrative staff, and 2 school committee representatives, as well as observations and documentation of leadership practices. Data analysis was conducted using thematic analysis techniques through the stages of data reduction, data presentation, and drawing conclusions, referring to the Miles and Huberman model. The results reveal a novel integrated leadership model that synthesizes Qur'anic principles with contemporary educational management practices. Specifically, this study contributes to Islamic educational leadership theory by: (1) demonstrating how the concept of "amanah" (trust) from Q.S. An-Nisa:58 is operationalized through transparent merit-based teacher placement and needs-based scholarship distribution, challenging traditional nepotistic practices; (2) proposing a "tri-dimensional justice framework" that distinguishes between distributive justice (resource allocation), procedural justice (decision-making processes), and interactional justice (interpersonal treatment) in madrasah governance; and (3) developing a "consultative-restorative leadership paradigm" that integrates shura (deliberation) mechanisms with restorative approaches to student discipline, moving beyond punitive models. This model demonstrates that Islamic educational leadership operates not merely as moral guidance, but as a systematic framework that simultaneously addresses spiritual development, organizational effectiveness, and social equity.